Repair of traumatic flank hernia with mesh strip suture: a case report - Shin Ae Lee; Ye Rim Chang (Journal of Trauma and Injury)
Traumatic flank hernia is a relatively rare hernia. We report a case of a male patient with severe multiple trauma, including abdominal injury, who presented with flank hernia 3 years postinjury. The hernia was successfully repaired using mesh strips suture, and at the 12-month follow-up, no complications or recurrence was found. Our findings indicate that when it is difficult to secure a sufficient operative field for mesh anchoring in a traumatic flank hernia, a technique of sutured repair with mesh strips may be considered as a treatment option as it requires less dissection. Compared to the conventional planar mesh repair, this technique decreases the risk of injuries and ischemic necrosis of the surrounding tissues.